Mortality in patients treated with extended duration dual antiplatelet therapy after drug-eluting stent implantation: a pairwise and Bayesian network meta-analysis of randomised trials. Issue 9985 (13th June 2015) - Palmerini, Tullio; Benedetto, Umberto; Bacchi-Reggiani, Letizia; Riva, Diego Della; Biondi-Zoccai, Giuseppe; Feres, Fausto; Abizaid, Alexandre; Hong, Myeong-Ki; Kim, Byeong-Keuk; Jang, Yangsoo; Kim, Hyo-Soo; Park, Kyung Woo; et al.
Summary: Background: Despite recent studies, the optimum duration of dual antiplatelet therapy (DAPT) after coronary drug-eluting stent placement remains uncertain. We performed a meta-analysis with several analytical approaches to investigate mortality and other clinical outcomes with different DAPT strategies. Methods: We searched Medline, Embase, Cochrane databases, and proceedings of international meetings on Nov 20, 2014, for randomised controlled trials comparing different DAPT durations after drug-eluting stent implantation. We extracted study design, inclusion and exclusion criteria, sample characteristics, and clinical outcomes. DAPT duration was categorised in each study as shorter versus longer, and as 6 months or shorter versus 1 year versus longer than 1 year. Analyses were done by both frequentist and Bayesian approaches. Findings: We identified ten trials published between Dec 16, 2011, and Nov 16, 2014, including 31 666 randomly assigned patients. By frequentist pairwise meta-analysis, shorter DAPT was associated with significantly lower all-cause mortality compared with longer DAPT (HR 0·82, 95% CI 0·69–0·98; p=0·02; number needed to treat [NNT]=325), with no significant heterogeneity apparent across trials. The reduced mortality with shorter compared with longer DAPT was attributable to lower non-cardiac mortality (0·67, 0·51–0·89; p=0·006; NNT=347), with similar cardiac mortality (0·93, 0·73–1·17; p=0.52). Shorter DAPT was also associated with a lower risk of major bleeding, but a higher risk of myocardial infarction and stent thrombosis. We noted similar results in a Bayesian framework with non-informative priors. By network meta-analysis, patients treated with 6-month or shorter DAPT and 1-year DAPT had higher risk of myocardial infarction and stent thrombosis but lower risk of mortality compared with patients treated with DAPT for longer than 1 year. Patients treated with DAPT for 6 months or shorter had similar rates of mortality, myocardial infarction, and stent thrombosis, but lower rates of major bleeding than did patients treated with 1-year DAPT. Interpretation: Although treatment with DAPT beyond 1 year after drug-eluting stent implantation reduces myocardial infarction and stent thrombosis, it is associated with increased mortality because of an increased risk of non-cardiovascular mortality not offset by a reduction in cardiac mortality. Funding: None.